Optimal Conduction Angle Control for Noise Reduction in xEV BLDC Wiper Motors - Jeong, Gi Heon; Oh, Yoon Gi; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2022)
This paper proposes optimal conduction angle for noise reduction in xEV BLDC wiper motors. Fuzzy logic simulation is performed to review the noise influences by conduction angle. After confirming that the current and torque ripple change according to the parameter change, and the optimized control method and parameters from the simulation to the controller is reflected. A test is conducted to reduce noise in a specific frequency range. Noise influences are verified through Fast Fourier Transform analysis on current wave forms and noise test results.
Keywords: BLDC wipe motor; Conduction angle; Conduction angle control; FFT-analysis; Fuzzy logic simulation; Noise FFT analyse; Noise influence; Wiper motors; XEV motor; BLDC wiper motor; Fuzzy control; Noise FFT analysis; Noise reduction; Wiper motor; xEV motor